The synthesis of ethical decision making for business professionals in small and medium sized enterprises (SMEs) / Khalizani Khalid - Khalid, Khalizani (2014)
The new approach to the field of ethical decision research deals with integrating moral philosophy theories into moral development theory, theory of reasoned action, stakeholder theory, and ethical leadership theory to study ethical decision making among business professionals in Malaysian. This study aims to examine the factors influencing ethical decision making in SMEs that has received almost no attention and failed to be addressed in previous studies. To ensure the compatibility and relevancy of the survey items, cognitive interviews with SMEs business professionals and focus groups discussions with relevant stakeholders were employed to determine significant design problems, to reduce inherent problems, and to reduce social-desirability bias before the survey is finalized. 340 responses from SMEs business professionals were tested using structural equation modelling to determine the best fit model. It is known that utilitarianism, deontology and virtue ethics, and ethical awareness, ethical judgment, and ethical intention are inter-related within the scope of moral philosophy and ethical decision making respectively. Additionally, this study found that moral philosophy, normative commitment, ethical leadership, perceived organizational support, and ethical work climate are positively and significantly influence ethical decision making. Hence, the findings provide greater insights into how moral philosophy determines the ethical values of business professionals with the influence of normative commitment, ethical leadership, perceived organizational support, and ethical work climate during the ethical decision making process.